1995
DOI: 10.1063/1.114295
|View full text |Cite
|
Sign up to set email alerts
|

Stability of nitrided silicon dioxide deposited by reactive sputtering

Abstract: The electrical properties of nitrided silicon dioxide formed by reactive sputtering in Ar/O2/N2 plasma from the SiO2 target have been studied. The nitrogen mixing ratio was varied from 0% to 15%, with the argon mixing ratio kept at 80%. It is found that as more nitrogen is incorporated, the leakage current increases for electron injection from both aluminum and silicon. By nitrogen reactive sputtering, the interface states generation during constant current stress is greatly reduced in comparison with oxide sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The on-current of the samples treated with HMDS was increased by 41%, compared to those without HMDS coating, and was almost three times larger than that of the samples without any surface treatment (1.69 μA). It had been reported that the low-temperature-deposited SiO 2 gate dielectric usually results in the higher gate leakage current during the high gate voltage biasing as a result of the SiO 2 with porous structure and lower atomic bonding energy [12,19,20]. The higher gate leakage current could decrease the drain current to result in the degraded device's electrical performance.…”
Section: Resultsmentioning
confidence: 99%
“…The on-current of the samples treated with HMDS was increased by 41%, compared to those without HMDS coating, and was almost three times larger than that of the samples without any surface treatment (1.69 μA). It had been reported that the low-temperature-deposited SiO 2 gate dielectric usually results in the higher gate leakage current during the high gate voltage biasing as a result of the SiO 2 with porous structure and lower atomic bonding energy [12,19,20]. The higher gate leakage current could decrease the drain current to result in the degraded device's electrical performance.…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of LPD are (1) low deposition temperature, (2) good step coverage, (3) high deposition rate, (4) good film quality, and (5) low cost. In particular, (1) and (3) are the major reasons why LPD could compete against PECVD and sputtering [6][7][8]. However, the surface of the plastic substrate does not have enough dangling bonds which would be attached to many semiconductor surfaces.…”
Section: Introductionmentioning
confidence: 98%
“…In the first case, oxide more sensitive to defect creation is needed to improve sensitivity, while in the latter, oxide more resistant to the damaging effects of irradiation is desirable. There are some publications addressing electrical hardness of sputtered oxide by thermal annealing [11] and by nitridation of sputtered and LPCVD oxides [12,13]. Since in MOS devices electrical hardness correlates well to irradiation hardness it is expected that nitridation of deposited oxide can give irradiation harder oxide films.…”
Section: Introductionmentioning
confidence: 98%